THE RELATIONSHIP BETWEEN SPIRITUAL INTELLIGENCE AND THE JUST ATTITUDE OF STUDENTS AT SMP RAHMAN WAHID MOJOGENENG - Taufiqillah Ridha Asfina; Chasiru Zainal Abidin; M. Ali Rohmad (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
Spiritual intelligence is closely related to how a person maintains the principles and responsibilities to carry out these principles while maintaining balance and creating appropriate value benefits. A person is not called spiritually intelligent, if he only cares about the hereafter but blinds himself to his mission in the world to Allah. Fair is a word that is quite difficult to describe, the meaning of fair is associated with law or something that is inherent in the rights of each individual. Fair is human values ​​and a pillar for aspects of life, both individuals, families and communities. The objectives of this study were: 1) to determine the spiritual intelligence of students at SMP Rahman Wahid Mojogeneng 2) to determine the fair attitude of students at SMP Rahman Wahid Mojogeneng 3) to test empirically the relationship between spiritual intelligence and fair attitude of students at SMP Rahman Wahid Mojogeneng. This research is a quantitative study with a correlation approach. The research population used was all students of SMP Rahman Wahid Mojogeneng. Sampling with stratified sampling technique was taken 34 students as respondents. Data collection using questionnaires, observation, and documentation. The results showed: 1) The spiritual intelligence of students at SMP Rahman Wahid Mojogeneng was generally in the high category with an average score of 36 because it was between the criteria for a score of 31 ≤ 40.2) The fair attitude of students at SMP Rahman Wahid Mojogeneng was generally included in moderate category with an average score of 37 because it is between the interval 31 ≤ 40. 3) There is a significant positive relationship between spiritual intelligence and fairness of students at SMP Rahman Wahid Mojogeneng with a correlation value of 0.618. The result of the correlation shows the level of correlation is strong with interpretation 0.610-0.800.